Chronic myeloid leukemia in a pediatric patient: a clinicopathologic case - Huerto-Aguilar, José L. (2022)
Chronic myeloid leukemia (CML) is a common myeloproliferative disease in adults, characterized by an overproduction of granulocytes in bone marrow as a consequence of the t(9:22)(q34;q11) translocation, known as Philadelphia chromosome. We present a case of CML in a 12-year-old male patient, who was admitted for outpatient care at the Alberto Sabogal Sologuren National Hospital. The clinical and laboratory findings of the case are described. Also, a general presentation of the disease is made and the differences between adult and pediatric CML are discussed, since it is a rare neoplasm in pediatric patients.